CHAIN SEPARATEDNESS IN A FAMILY COVERINGS SPACE - Misajleski, Zoran; Velkoska, Aneta; Durmishi, Emin (Matematichki Bilten, 2024)
The paper gives a generalization of dierent kind of separatedness and chain separatedness of a topological space to a family coverings space that is more general than a topological space and it consists of a set and a family of coverings of the set.